Turmeric-black pepper-honey nanoemulsion formulation and antiulcerogenic effect evaluation against ethanol-induced gastric ulcers in rats. - Amirah Adlia; Cynthiana Christabella Aslan; Lia Safitri; I Ketut Adnyana (PLoS ONE)
Gastric ulcer is a common disorder of the digestive system. The combination of turmeric and honey is known to treat stomach ulcers. However, curcumin, an active component in turmeric, has limitations, i.e., poor water solubility and low oral bioavailability. Therefore, turmeric and honey were formulated into a nanoemulsion with black pepper to enhance curcumin bioavailability. The study followed a systematic approach to optimize the nanoemulsion formula, determine stability, and evaluate ulcer healing activity in rats with ethanol-induced gastric ulcers. Nanoemulsion was prepared using a low-energy emulsification method called emulsion phase inversion (EPI). Two stability evaluations were carried out, i.e., storage and freeze-thaw stability tests. The organoleptic, droplet size, polydispersity index, pH, viscosity, and curcumin content of the nanoemulsion were evaluated. Male Wistar albino rats were induced with 96% ethanol for six days. The rats were divided into six groups, i.e., healthy control, ulcerated control, omeprazole, two different doses of turmeric, honey, and black pepper nanoemulsion (NTBH1 and NTBH2), and turmeric and honey nanoemulsion (NTH). The antiulcer activity was determined by measuring the ulcer area, ulcer index, curative index, ulcer severity score, and histology. The best formula with the smallest droplet size, i.e., 144.6±3.8 nm, was obtained from the nanoemulsion using Tween 80 as surfactant, glycerin as cosolvent, and sodium alginate as viscosity enhancer. The result showed that the nanoemulsion was stable after being stored at 25 and 40°C for four weeks and after six cycles of freeze-thaw test. The ulcer index of the ulcerated rats from the lowest to the highest, i.e., NTBH2, omeprazole, NTH, and NTBH1. In conclusion, the nanoemulsion developed in this study containing turmeric, honey, and black pepper holds promising potential in treating gastric ulcers, offering a hopeful outlook for future treatments.